Analisa Fatwa MUI Tentang Aborsi - Sa’adah, Mazro’atus (Qolamuna : Jurnal Studi Islam, 2018)
This Paper discusses about the abortion fatwa issued by the Indonesian Council of Ulama (MUI). The MUI issued a fatwa twice about abortion. In this fatwa, the MUI considers emergency aspects (darurat and hajat). Basically, the law of abortion is unclean (haram), both before this spirit is blown and after it. However, in certain conditions, especially those related to the interets of the mother and baby from the medical side, including in the case of abortion due to rape, so abortion is allowed before the age 40 days or still in the germ (nutfah) phase. Keywords : Fatwa MUI, abortion